Cognizing the crystallization aspects of NaCaPO4 concomitant 53S bioactive-structures and their imprints in in vitro bio-mineralization. (4th August 2021) - Riju Chandran, R.; Chitra, S.; Vijayakumari, S.; Bargavi, P.; Balakumar, S.
Abstract : Compositional and bio-physico-chemical characteristic features of bioactive glasses are of great importance in biomedical field. Abstract : Compositional and bio-physico-chemical characteristics of bioactive glasses are of great importance for their applications in medicine. For the first time, herein we report the single crystalline phase NaCaPO4 in 53S bioglass which is mainly achieved by sol–gel chemistry and processing parameters. The bioactive material sintered at 700 °C revealed a NaCaPO4 crystalline phase with nominal deviation. Dominance of bridging oxygen is observed in 53S-700 through high resolution XPS spectroscopy which supports the XRD results in terms of exact crystal structure formation (NaCaPO4 ). The dominant Q 4 Si–O–Si stretching in the 700 °C heat treated bioglass exhibits bonding with bridged oxygen confirmed through functional group analysis. A triangular platelet-like structure and spherical morphology are visible in the synthesized bioactive materials. A comparatively elevated mechanical stability is achieved in the 700 °C sintered bioglass with respect to compactness in the crystal structure. The spiky rod-like apatite precipitation and dominant Ca5 (PO4 )3 (OH) phase symbolize the prominent mineralization behavior of the bioglass heat treated at 750 °C due to the rapid ionic release from the material. On the whole, development of pristine NaCaPO4 in the 53S bioglass matrix encourages researchers to analyze the bio-chemical features of this material focusing on bone regeneration.